Launching KISM - the Knowledge Platform for Inclusive and Sustainable Food Markets and Value Chains - Malhotra, Swati (International Food Policy Research Institute, 2023)
Food systems transformation is crucial for more inclusive, equitable and sustainable food markets and value chains. The food sector makes up one-fifth of the global economy. It’s the world’s largest source of employment (50% of the global workforce) and the livelihoods of most poor people depend on it. The food sector contributes to around 33% of total GHG emissions and is vulnerable to climate-induced supply disruptions that can affect global food security.